2019
DOI: 10.1111/1467-9566.12983
|View full text |Cite
|
Sign up to set email alerts
|

The development of the new assistant practitioner role in the English National Health Service: a critical realist perspective

Abstract: Adopting a critical realist perspective, this article examines the emergence of a relatively new non‐professional healthcare role, the assistant practitioner (AP). The role is presented as a malleable construct cascading through and sensitive to structure–agency interaction at different levels of NHS England: the sector, organisation and department. At the core of the analysis is the permissiveness of structures established at the respective levels of the NHS, facilitating or restricting agency as the role pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, Kessler and colleagues (2015) studied task reallocation from nurses to nursing assistants in England and found that joint working occurred where nurses supported a ‘specialist‐discard’ logic — aiming to enhance their professional status by transferring lower‐status tasks like washing patients to nursing assistants — instead of a more traditional ‘hoarding’ logic — where nurses claimed control over all tasks, resisting collaboration with nursing assistants. Over time, English nurses’ gradual turn to a specialist‐discard logic facilitated the growth of an extensive nursing assistant workforce and alternative nursing roles like assistant practitioners (Kessler & Spilsbury, 2019). Other studies have highlighted the increasingly active role of managerial supports like career structures (Bach et al., 2008).…”
Section: Perspectives On New Work Rolesmentioning
confidence: 99%
“…For example, Kessler and colleagues (2015) studied task reallocation from nurses to nursing assistants in England and found that joint working occurred where nurses supported a ‘specialist‐discard’ logic — aiming to enhance their professional status by transferring lower‐status tasks like washing patients to nursing assistants — instead of a more traditional ‘hoarding’ logic — where nurses claimed control over all tasks, resisting collaboration with nursing assistants. Over time, English nurses’ gradual turn to a specialist‐discard logic facilitated the growth of an extensive nursing assistant workforce and alternative nursing roles like assistant practitioners (Kessler & Spilsbury, 2019). Other studies have highlighted the increasingly active role of managerial supports like career structures (Bach et al., 2008).…”
Section: Perspectives On New Work Rolesmentioning
confidence: 99%
“…Such findings resonate with the experiences of other front‐line health‐care workers, whose roles were shaped in nuanced ways by local contexts (Gale et al., 2018 ). For assistant physicians in the UK, routines became a balance between individual agency and structural permissiveness, whilst national policy also played an important part (Kessler & Spilsbury, 2019 ). To date, the impact of wider policy evolution on the nature of link working does not appear to have been explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Professional jurisdictions and boundaries are critical factors in the configuration of health care. Accordingly, they are important for the organisation of care and a complex aspect of healthcare planning and management (Abbott, 1988, Currie et al ., 2010, Huby et al ., 2014, Jones et al ., 2019, Kessler and Spilsbury, 2019, Nancarrow and Borthwick, 2005). Moreover, as the paper will show, professional boundaries influence day‐to‐day professional practice, collaboration and care delivery (Cramer et al ., 2018, McMurray, 2011, Salhani and Coulter, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Changes particularly involve the construction of new professional categories and flexible work roles to cater for patient‐related needs in healthcare organisations. Kessler and Spilsbury (2019) suggest that the development of new work roles is among the most challenging types of healthcare change. However, while professional work and roles, opportunities for professionalisation as well as professional boundaries are under development due to transformations in the professional environment, this development is concurrently curtailed by the continuous struggle for upholding institutionalised professional boundaries (Currie et al ., 2012, McMurray, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation